TANTANGAN DALAM PERLUASAN UNI EROPA KE NEGARA-NEGARA EROPA TENGAH DAN TIMUR - Chandrawati, Nurani (Global: Jurnal Politik Internasional, 2004)
This article tries to explain several challenges that must be faced by European Union (EU) about its decision to enlarge its membership by admitting eight Central and Eastern European Countries (CEECs) on May 1st, 2004. This is not an easy decision, because the eight new members from CEECs are still going through a transformation period. An interesting question derived from this phenomena is whether the entry of eight CEECs into the EU will increase EU's level of integration into federalism or, on will the contrary, add many new problems for the integration process. Overall, there are three challenges facing the European Union in its sixth enlargement process by admitting eight CEECs. The first challenge is the alleged negative motivation of the new members; second, the problem of decision making process inside EU institutions; and thirdly, financial burden caused by the funding of transformation processes in the eight CEECs. Altogether, these challenges will lead EU into intergovernmentalism and not federalism, which might be the prominent desire of EU's founding fathers.